Off-label use of antibiotics in hospitalised children in a tertiary care teaching hospital - ., Puja; D. C., Dhasmana; Kohli, Saurabh; Chander, Vipin (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Children constitute one-third of the population and they suffer from a variety of infectious diseases and are commonly prescribed antibiotics. Most of the antibiotics lack sufficient information on safety and efficacy in children and are thus prescribed off-label. This study was envisaged to assess the off-label use of antibiotics in hospitalized children. Methods: Total 120 patients were included in the study. Off-label use was determined on the basis of product literature and National Formulary of India. Descriptive statistics was used to present the data i.e. percentage; proportions, frequency, mean and standard deviation using Microsoft excel worksheet. Results: A total of 791 drugs from different classes were prescribed to 120 patients with a mean of 6.6±2.68 drugs described per patient during their stay in the hospital. 100 out of 120 (83%) patients were prescribed at least one antibiotic during their stay in the hospital. Out of the 204 antibiotics prescribed, 43(21%) were prescribed off-label. Antibiotic dose was the most common reason followed by age (1month-1 year more than 2-6 years of age) and frequency in off-label use. Conclusions: Antibiotics are commonly prescribed to children with substantial off-label use. The same must be seriously addressed by the policy makers and stakeholders in order to promote their rational use.